Adaptations of Luzula confusa to the Polar Semi-Desert Environment - Addison, P.A.; Bliss, L.C. (ARCTIC, 1984)
Luzula confusa is both morphologically and physiologically adapted to the polar semi-desert environment of the western Queen Elizabeth Islands. This species combines the more efficient graminoid photosynthetic system and a less drought-resistant mechanism with some of the cushion plant energy-trapping characteristics such as tufted growth form and persistence of dead leaves, with consequent thicker boundary layer. In this manner, the plant is able to assimilate carbon throughout the 24-hr arctic day. The species utilizes the most favorable part of the growing season by rapid initiation of growth via relatively high photosynthetic rates, especially at low temperatures. This species is very responsive (net assimilation rates) to small changes in leaf temperature and leaf water potential. This permits the species to take advantage of small rises in leaf temperature (leaves normally 5 to 8 degrees C) and to adjust to high VPD and low leaf water potential during the occasional drought. The slow-growing, long-living conservative strategy of this species appears ideally suited to areas that are limited in their vascular plant cover because of rigorous environments. Within the range of habitats available, Luzula confusa predominates in sites of intermediate moisture with abundant cryptogams. It does not occur in the polar deserts with their drier surface soils except in snowflush communities.Key words: Luzula confusa, High Arctic, plant/water relations, net photosynthesis, plant phenology, polar semi-deserts Mots clés: Luzula confusa, nord de l'Arctique, relations plantes-eau, photosynthèse nette, phénologie des plantes, semi-déserts polaires